Role and response of primary healthcare services in community end-of-life care during COVID-19: Qualitative study and recommendations for primary palliative care delivery. (February 2023) - Turner, Nicola; Wahid, Aysha; Oliver, Phillip; Gardiner, Clare; Chapman, Helen; Khan (PPI co-author), Dena; Boyd, Kirsty; Dale, Jeremy; Barclay, Stephen; Mayland, Catriona R; Mitchell, Sarah J
Background: The need for end-of-life care in the community increased significantly during the COVID-19 pandemic. Primary care services, including general practitioners and community nurses, had a critical role in providing such care, rapidly changing their working practices to meet demand. Little is known about primary care responses to a major change in place of care towards the end of life, or the implications for future end-of-life care services. Aim: To gather general practitioner and community nurse perspectives on factors that facilitated community end-of-life care during the COVID-19 pandemic, and to use this to develop recommendations to improve future delivery of end-of-life care. Design: Qualitative interview study with thematic analysis, followed by refinement of themes and recommendations in consultation with an expert advisory group. Participants: General practitioners ( n  = 8) and community nurses ( n  = 17) working in primary care in the UK. Results: General practitioner and community nurse perspectives on factors critical to sustaining community end-of-life care were identified under three themes: (1) partnership working is key, (2) care planning for end-of-life needs improvement, and (3) importance of the physical presence of primary care professionals. Drawing on participants' experiences and behaviour change theory, recommendations are proposed to improve end-of-life care in primary care. Conclusions: To sustain and embed positive change, an increased policy focus on primary care in end-of-life care is required. Targeted interventions developed during COVID-19, including online team meetings and education, new prescribing systems and unified guidance, could increase capacity and capability of the primary care workforce to deliver community end-of-life care.